Early surgical outcomes of 550 consecutive patients treated for benign gynecological conditions by transvaginal natural orifice transluminal endoscopic surgery - Yannick Hurni; Colin Simonson; Marcello Di Serio; Régine Lachat; Pauline Bodenmann; Stéphanie Seidler; Daniela Huber (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Evidence about intra‐ and postoperative complication rates related to transvaginal natural orifice transluminal endoscopic surgery (vNOTES) for benign gynecological conditions is still limited. We report and analyze data from a large cohort of patients operated in a single institution during 3.5 years. Material and Methods To evaluate the safety and feasibility of vNOTES for benign gynecological indications, we performed a single‐center observational study reporting and analyzing perioperative outcomes of 550 consecutive patients operated between 2020 and 2024. Results Of the 550 included patients, 365 (66.4%) underwent a vNOTES hysterectomy, 167 (30.4%) a procedure limited to the adnexa, and 18 (3.3%) other interventions, including myomectomy, pelvic adhesiolysis, post‐hysterectomy pelvic hematoma drainage, pelvic organ prolapse repair, and appendectomy. The mean age was 49.4 ± 12.2 years, and the mean BMI was 26.2 ± 5.8 kg/m2. The total complication rate was 6.5% (36 cases), of which 2.7% (15 cases) were intraoperative complications and 4.0% (22 cases) were postoperative complications. Patients presented postoperative complications classified as Clavien–Dindo (CD) grade I in 4 cases (0.7%), grade II in 10 cases (1.8%), and grade III in 8 cases (1.5%). We observed no CD grade IV and V complications. Three patients (0.5%) were rehospitalized for postoperative complications management. The conversion rate was 1.6%, with nine cases of conversion to conventional laparoscopy and none to laparotomy. Conclusions The application of vNOTES appears safe and feasible for most benign gynecological surgeries. Our study focused on surgical complications and demonstrated a profile similar to those reported in previous studies.